2020
DOI: 10.21203/rs.3.rs-94544/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinicopathological Factors and Prognosis of Massive Hemorrhage After Radiotherapy for Nasopharyngeal Carcinoma

Abstract: Background: To investigate the clinicopathological factors and prognosis of nasopharyngeal hemorrhage after radiotherapy for nasopharyngeal carcinoma (NPC). Methods: The clinicopathological data of 539 NPC patients who received radiotherapy were analyzed retrospectively, including gender; age; T-stage; N-stage; pathological type; type of radiotherapy; synchronous chemotherapy; secondary-course radiotherapy; radioactive skull base osteonecrosis; diabetes, hypertension, or other systemic diseases; results of nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In our study, 56% of patients had a relapsed rT4 tumor and tumors initially classified as T3 or T4 relapsed as rT3 or rT4 tumors in 85.7% of cases. Wang et al 13 found in a retrospective study that T4 tumors were associated with a significant risk of LR relapse and that T stage was the only factor correlated with relapse.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 56% of patients had a relapsed rT4 tumor and tumors initially classified as T3 or T4 relapsed as rT3 or rT4 tumors in 85.7% of cases. Wang et al 13 found in a retrospective study that T4 tumors were associated with a significant risk of LR relapse and that T stage was the only factor correlated with relapse.…”
Section: Discussionmentioning
confidence: 99%